The Green Symphony: A Phenomenological Study of Environmental Awareness and Green Purchase Decisions Among Women in MSMEs - M. Ilham Wardhana Haeruddin (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to explore the environmental awareness of women who are owners and employees of Micro, Small, and Medium Enterprises (MSMEs) in Makassar City and its influence on their green product purchase decisions. Employing a qualitative phenomenological approach, this research involved six participants selected through purposive sampling: three MSME owners and three employees who actively make purchasing decisions related to business operations. Data were collected through in-depth interviews, participant observation, and document review. Thematic analysis following the Miles, Huberman, and Saldaña model was employed, with data validity ensured through source triangulation and member checking. The findings reveal four major themes: (1) multilevel environmental awareness encompassing individual, social, and institutional dimensions; (2) green purchase decision-making process driven by intrinsic values and contextual factors; (3) barriers to green consumption including price sensitivity, limited product availability, and information asymmetry; and (4) the role of women's leadership within MSME ecosystems as catalysts for sustainable consumption practices. This research contributes theoretically to the green consumer behavior literature by integrating the Theory of Planned Behavior (TPB) and value-belief-norm theory within an Indonesian MSME context. Practically, the findings have implications for sustainability-oriented human resource management in small enterprises and inform policy frameworks supporting green economic transformation in emerging markets.